Inclusion and Political Representation in Peace Negotiations: The Case of the Colombian Victims' Delegations. Issue 3 (December 2019) - Mendes, Isa
This article discusses the issue of inclusion in peace negotiations, in particular the Colombian peace process with the Fuerzas Armadas Revolucionárias de Colombia, with special emphasis to a perceived tension between "direct" and "indirect" inclusive initiatives. It argues that, as currently discussed by the Peace and Conflict literature, inclusion tends to be seen as neutral and benign, which leaves little room for critical discussions about the political contention behind peace negotiations deemed "inclusive." It thus proposes to discuss inclusion through the theoretical lens of political representation and apply such reflections to the specific case of the Colombian victims' delegations that travelled to Havana in 2014 in order to take part in the table's discussions on the victims and transitional justice topic. Ultimately, I will argue there was simultaneous utilisation and rejection of the language of representation.